Analysis on Bi2Te3 thermoelectric cooler with silica aerogel encapsulation. (October 2015) - Hu, H.M.; Ge, T.S.; Dai, Y.J.; Wang, R.Z.
Highlights: A Bi2 Te3 TEC with silica aerogel encapsulation is proposed. A three dimensional model for the TEC is developed. This model first considers the effect of air gap and aerogel. Different thicknesses of aerogel encapsulation for TEC are discussed. Abstract: A Bi2 Te3 TEC with silica aerogel encapsulation is developed. Silica aerogel with different thicknesses is filled in the void spaces around the TE legs and started from cold-side ceramic plate. A three dimensional mathematical model for the TEC is developed. This model considers the effect air gap and silica aerogel. (Bi0.2 Sb0.8 )2 Te3 and Bi2 (Te0.97 Sb0.03 )3, which have temperature-dependent TE properties, are selected to be p-type and n-type TE materials. Also, an experimental test bench is built to validate the three dimensional model. The performances of non-silica aerogel encapsulated TEC with and without consideration of air gap are investigated. Meanwhile, the effects of different thicknesses of silica aerogel encapsulation under different Ta s and Va s are analysed. The results show that the cold side ceramic and interconnector, and cold part of TE legs can be insulated effectively while the hot part of TE legs can be effectively dissipated using part silica encapsulation when Th ⩾ Ta ⩾ Tc . The maximum Qc at Laer = 0.8 mm is nearly increased by 7% as compared with that at Laer = 0 mm when Ta = ( Tc + Th )/2. Moreover, apart from the cold side interconnector, Laer should be about 2%, 15% and 25% of the Lleg corresponding to the maximum Qc condition when Ta = Tc, Ta = ( Th + Tc )/2 and Ta = Th, respectively. The value of Laer can be ( Ta − Tc )/( Th − Tc ) Lleg corresponding to the optimum COP condition.